An Intelligent Robust Control of Wheeled Mobile Robot in Restricted Environment - Ali, Mohammed A. H.; Musa, Mailah; Wan Azhar, Wan Yusoff; Zamzuri, Hamedon; Zulkifli, Md. Yusof (IARAS, 2017)
This paper presents a simulation study of hybrid control strategy to control the motion of wheeled mobile robot (WMR) in the restricted environment. The implementation of the robot path planning in restricted environments needs a suitable robust controller to avoid known/unknown disturbances and guarantee zero track errors. A proportional derivative active force control (PDAFC) scheme is incorporated with artificial intelligent techniques, namely, fuzzy logic (FL) to effectively estimate the actual torque applied on the robot wheels. Several kinds of trajectories in the restricted environment with unexpected changes in their trajectory has been used to test the proposed control system. The simulation study was carried out using software interface (MATLAB / SIMULINK). The results demonstrate a better performance and higher capability of PDAFC controller for disturbance rejection in comparison with PD and AFC controllers.